Five Key Words for Effective Governance. Issue 136 (November 2014) - Hull, Ted
<x xml:space="preserve">Abstract</x> Policy Governance® consultant and practitioner Ted Hull applies his love of analogies (while recognizing that they can never be perfect) to help us understand the basics of good governance.